2019
DOI: 10.1177/1099636219838446
|View full text |Cite
|
Sign up to set email alerts
|

Shear-based vibration control of annular sandwich plates using different piezoelectric fiber composites: A comparative study

Abstract: This work presents the shear-based attenuation of vibration of an annular sandwich plate using two different shear mode piezoelectric fiber composite (PFC) actuators namely Shear Actuated Fiber Composite (SAFC) and Balanced Laminate of PFC (BL-PFC). A conventional shear mode monolithic piezoelectric (PZT5H) actuator is also used, and a comparative study on the shear actuation capabilities of all three shear actuators is performed to address the best one for shear-based control of the annular sandwich plate. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…With respect to the sandwich structures, alongside the method of bonding the piezoelectric materials to surface of the structure, there is the option of directly integrating the piezoelectric material into the structure (in the manner of piezofibers or piezoelectric plates). On this line, the vibration control of an annular sandwich plate with shear mode piezoelectric actuators was investigated analytically and numerically [26]. In the study, three different shear actuators were analyzed; two of which were piezofiber composites and the other was a PZT-5H based shear actuator.…”
Section: Avc Of Beams and Platesmentioning
confidence: 99%
“…With respect to the sandwich structures, alongside the method of bonding the piezoelectric materials to surface of the structure, there is the option of directly integrating the piezoelectric material into the structure (in the manner of piezofibers or piezoelectric plates). On this line, the vibration control of an annular sandwich plate with shear mode piezoelectric actuators was investigated analytically and numerically [26]. In the study, three different shear actuators were analyzed; two of which were piezofiber composites and the other was a PZT-5H based shear actuator.…”
Section: Avc Of Beams and Platesmentioning
confidence: 99%
“…The proposed MFC structure interaction model agreed well with experiments and numerical simulations of models. Dubey et al [25] studied the shear-based attenuation of the vibration of an annular sandwich plate using shear actuated fiber composite (SAFC) and balanced laminate of PFC (BL-PFC) methods. The results showed that the BL-PFC is the best for shear-based attenuation of vibration of the annular sandwich plate.…”
Section: Introductionmentioning
confidence: 99%